The role of information asymmetry in financing methods - Salehi, Mahdi (Managing global transitions, 2014)
There is no doubt that new investments are the cornerstone of progress and competition in today's world. Different financing instruments are employed to secure the funds for these investments. The most common financing methods in Iran are debt and equity financing. Some investors, including corporate insiders, have access to private information. The more private the information, the more will be the bid/ask spread between investors, thus reducing the returns of those with no access to such information. Therefore, information asymmetry is expected to affect the funding of investments. The purpose of this study was to examine the relationship between information asymmetry and financing methods (debt and equity financing). The population consists of all the firms listed on the Tehran Stock Exchange that have been operating during the period 2006-2010. Totally, 61 firms were selected as sample using targeted sampling. The results showed that there is no significant relationship between information asymmetry and debt financing; however, there was a significant positive relationship between information asymmetry and equity financing.
Keywords: Das Kapital; information asymmetry; kapital; poslovne finance; debt financing; equity financing; investicije; dolgovi; informacije; asimetrija